Detection of Human Leukocyte Antigen and Celiac Disease Auto Antibodies in serum of Patients with Multiple Sclerosis - S. Aboud, Rana; K. Ismael , May; J.Mohammed, Haider (Iraqi Journal of Science, 2026)
To determine the important pathogenic role of celiac disease in triggering severalautoimmune disease, thirty patients with Multiple Sclerosis of ages (22-55) yearshave been investigated and compared with 25 healthy individuals. All the studiedgroups were carried out to measure anti-tissue transglutaminase antibodies IgA IgGby ELISA test, anti-reticulin antibodies IgA and IgG, and anti-endomysialantibodies IgA and IgG by IFAT. There was a significant elevation in theconcentration of anti-tissue transglutaminase antibodies IgA and IgG compared tocontrol groups (P≤0.05), there was 4(13.33%) positive results for anti-reticulinantibodies IgA and IgG , 3(10%) positive results for anti-endomysial antibodiesIgA and IgG . There were 4 positive results (13.33%) for HLA-DQ8 by using HLADQ8 Real-Time PCR test. These results indicated that patients with celiac diseaseplay an important role in pathogenesis of Multiple Sclerosis.